The Effect of Pumpkin Fruit Ripeness (Cucurbita moschata. D) on Total Flavonoid Levels and Antioxidant Activity - Astutik, Linda; Yanti, Eka Fitri (Biology, Medicine, & Natural Product Chemistry, 2023)
Pumpkin fruit (Cucurbita moschata. D) belongs the Cucurbitaceae family which is a functional vegetable widely distributed in Indonesia because it has nutritional value and health benefits. This study aims to determine the value of total flavonoid content and antioxidant activity in the ethanol extract of unripe, mature and ripened pumpkin. Simplicia powder was extracted by maceration method using 96% solvent. Testing the total flavonoid content with the addition of AlCl3 at a wavelength of 425 nm and the antioxidant activity test was carried out using DPPH (1-1-diphenyl-2-picrylhydrazyl) as a free radical with a maximum wavelength of 515 nm using microplate reader. The results of the study concluded that the ethanolic extract of pumpkin flesh had a total flavonoid content of 0,146 mgQE/100g in unripe fruit, 0,221 mgQE/100g in mature pumpkin, 0,191 mgQE/100g in ripened pumpkin. The antioxidant activity of the ethanol extract of unripe, mature, and ripened pumpkin fruit obtained was not active or did not completely reduce free radicals.